Direct torque control induction motor drives - Mat Husin, Azman (2014)
This paper presents an implementation of a direct torque control (DTC) strategies to control the operation induction motor (IM). The aim is to control effectively the torque and flux. Torque control of an induction motor base on DTC strategy has been developed and a comprehensively study in this thesis. Direct torque control is the first technology to control the real motor control variable of torque and flux. This method made the motor more accurate and fast torque control, high dynamic speed response and simple to control. This report presents a principle of the DTC; switching table, and selection of the amplitude of the hysteresis band of torque and flux. The basic dynamic performance of DTC is investigated. The performance is including in when the motor in starting drives and when motor in nominal value. The performance of this control method has been demonstrated by simulation using a versatile simulation package, MATLAB/SIMULINK. The author also present the simulation results related to the theoretical aspects mentioned in the paper. The result shows that the proposed direct torque control is capable to control the operation of the induction motor